2020
DOI: 10.3390/bdcc4040028
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Blockchain in Internet of Things and AI

Abstract: The Internet of Things (IoT) represents a new technology that enables both virtual and physical objects to be connected and communicate with each other, and produce new digitized services that improve our quality of life. The IoT system provides several advantages, however, the current centralized architecture introduces numerous issues involving a single point of failure, security, privacy, transparency, and data integrity. These challenges are an obstacle in the way of the future developments of IoT applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(45 citation statements)
references
References 73 publications
0
45
0
Order By: Relevance
“…For this incident, Professor David Brock and Sanjay Sharma suggested RFID tags to track the different items in the distribution chain in which they decided to use the very bar code tags to monitor the items to save the price of the service and to manufacture more complex shapes with bigger, more costly memory capacity. e FID tags associated with the data link have been placed in the database and accessible via the Internet [7]. A few research and journals have reported that Ashton, Executive Director, in MIT ID Centre in1999, first launched the Internet of ings [8,9].…”
Section: Background Of Iot-enabled Disaster Managementmentioning
confidence: 99%
“…For this incident, Professor David Brock and Sanjay Sharma suggested RFID tags to track the different items in the distribution chain in which they decided to use the very bar code tags to monitor the items to save the price of the service and to manufacture more complex shapes with bigger, more costly memory capacity. e FID tags associated with the data link have been placed in the database and accessible via the Internet [7]. A few research and journals have reported that Ashton, Executive Director, in MIT ID Centre in1999, first launched the Internet of ings [8,9].…”
Section: Background Of Iot-enabled Disaster Managementmentioning
confidence: 99%
“…To tackle a challenging hurdle to compute offloading and resource allocations in a dynamic environment, a deep reinforcement learning approach can be used. Furthermore, blockchain can secure and optimize offloading issues in multi-UAV (unmanned aerial vehicles) aided mobile edge computing architecture [61][62][63][64].…”
Section: • Mobile Edge Networkmentioning
confidence: 99%
“…Layered architectures and their objectives/functions or goals are discussed in various literature and have slight variations. In this regard, Figure 1 presents a generalized literature study result to identify various IoT architecture models [9], [14], [18], [64], [65]. In general, five-tier, four-tier, and three-tier are distinguished from the pool of proposed architectures.…”
Section: Iot Operation Over Blockchain-based Architecturementioning
confidence: 99%
“…Given that IoT technology is evolving rapidly, a simple three-tier model can not provide a sufficiently accurate abstraction. The next model under consideration is four-tier [64]. The apparent difference from the previous architecture This work is licensed under a Creative Commons Attribution 4.0 License.…”
Section: Iot Operation Over Blockchain-based Architecturementioning
confidence: 99%